IMPLEMENTASI VLAN (VIRTUAL LOCAL AREA NETWORK) PADA RUMAH SAKIT MATA RAMATA - Yoga, Bhaskara Budi; Raharja, Made Agung (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
Ramata Eye Hospital is an eye hospital that is still under construction, both in terms of building, technical, and system. This research will discuss system development in this hospital network with the aim of optimizing data communication in this hospital later when it starts operating. This research focuses on discussing VLAN configuration which plays an important role in optimizing data communication later. VLAN is a network model that divides networks logically into several different VLANs. VLAN is not limited to physical network conditions such as on a LAN, VLAN can be configured virtually without having to look at the condition of the equipment, so VLANs have flexibility in network settings and make it easier for network administrators to share their network according to the network security functions and needs. Because of that, Ramata Eye Hospital really needs a VLAN in data communication later, which in addition to saving VLAN space can also save costs because it does not need to use many switches for network purposes at this Hospital.